Do environmental risk factors for the development of psychosis distribute differently across dimensionally assessed psychotic experiences? - Cosgrave, J; Purple, RJ; Haines, R; Porcheret, K; van Heugten-van der Kloet, D; Johns, L; Alexander, I; Goodwin, GM; Foster, RG; Wulff, K (Springer Nature, 2021)
Psychotic experiences (PE) are associated with poorer functioning, higher distress and the onset of serious mental illness. Environmental exposures (e.g. childhood abuse) are associated with the development of PE. However, which specific exposures convey risk for each type or dimension of PE has rarely been explored. The Oxford Wellbeing Life and Sleep (OWLS) survey includes 22 environmental risk factors for psychosis and was designed to examine how environmental risks are associated with specific dimensions of PE. Multivariate logistic regression models were fit using these risk factors to predict six dimensions of PE (perceptual abnormalities, persecutory ideation, bizarre ideas, cognitive disorganisation, delusional mood and negative symptoms). Models were built using only 70% of the data, and then fit to the remaining data to assess their generalisability and quality. 1789 (27.2% men; mean age = 27.6; SD = 10.9) survey responses were analysed. The risk factors predictive of the most PE were anxiety, social withdrawal during childhood and trauma. Cannabis and depression predicted three dimensions with both predicting bizarre ideas and persecutory ideation. Psychological abuse and sleep quality each predicted two dimensions (persecutory ideation and delusional mood). Risk factors predicting one PE dimension were age (predicting cognitive disorganisation), physical abuse (bizarre ideas), bullying and gender (persecutory ideation); and circadian phase (delusional mood). These results lend support for a continuum of psychosis, suggesting environmental risks for psychotic disorders also increase the risk of assorted dimensions of PE. Furthermore, it advocates the use of dimensional approaches when examining environmental exposures for PE given that environmental risks distribute differently across dimensions.